2019
DOI: 10.1186/s42466-019-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Anodal tDCS over left parietal cortex expedites recovery from stroke-induced apraxic imitation deficits: a pilot study

Abstract: Background: To date, specific therapeutic approaches to expedite recovery from apraxic deficits after left hemisphere (LH) stroke remain sparse. Thus, in this pilot study we evaluated the effect of anodal transcranial direct current stimulation (tDCS) in addition to a standardized motor training on apraxic imitation deficits. Methods: In a rehabilitation hospital, we assessed apraxic, aphasic, and motor deficits in 30 LH stroke patients before and after a five-day standard programme of motor training combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…A considerable number of studies in healthy and pathological aging have shown encouraging results for application of tDCS to counteract age-associated decline in various functional domains [78][79][80][81]. Moreover, tDCS has been suggested to be effective in treating symptoms in patients with brain lesions after stroke [82][83][84][85], or in Parkinson´s disease [85], which often develop in higher age. However, despite promising findings described in these studies, a lack of positive functional effects of tDCS were also reported in older adults [24,25,[86][87][88], which might be due to the application of suboptimal stimulation protocols.…”
Section: Proposed Mechanistic Foundationsmentioning
confidence: 99%
“…A considerable number of studies in healthy and pathological aging have shown encouraging results for application of tDCS to counteract age-associated decline in various functional domains [78][79][80][81]. Moreover, tDCS has been suggested to be effective in treating symptoms in patients with brain lesions after stroke [82][83][84][85], or in Parkinson´s disease [85], which often develop in higher age. However, despite promising findings described in these studies, a lack of positive functional effects of tDCS were also reported in older adults [24,25,[86][87][88], which might be due to the application of suboptimal stimulation protocols.…”
Section: Proposed Mechanistic Foundationsmentioning
confidence: 99%
“…We assume that the verum stimulation (anodal tDCS over the left parietal lobe) leads to a more significant improvement in apraxia severity than sham stimulation [ 1 ]. The primary endpoint is the difference in the total score of the Cologne Apraxia Screening (KAS [ 19 ]) between the post-interventional investigation and baseline.…”
Section: Methodsmentioning
confidence: 99%
“…A pilot study following the identical interventional and training procedure was performed before this RCT [ 1 ]. Here, 20 apraxic patients showed a standard deviation (SD) of about 7 points in the comparison of the KAS-score between baseline and post-interventional assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect correlated with measures of transcallosal connectivity in the splenium corporis callosi to the IPL-L pointing to an interhemispheric facilitation of this area. Furthermore, it was shown in stroke patients, that the excitatory stimulation by tDCS of the lesioned posterior parietal cortex improved the performance of gestural imitation (Bolognini et al, 2015;Ant et al, 2019).…”
Section: Introductionmentioning
confidence: 99%